ON THE ISSUE OF NATIONAL EXILE AND SELF-EXILE IN FRANCE BEVK'S HISTORICAL NOVEL MAN AGAINST MAN (Philological Studies, 2020)
In the paper, the problem of exile is first understood in the way of national exile and persecution. The analysis will focus on the historical novel Človek proti človeku [Man against Man], 1930, by France Bevk, which thematizes the Middle Ages, but which should be read as a metaphor through which the author during the Italian occupation of Primorsko polemically and subtle confronted foreign rulers. In the novel the problem of national persecution is represented as the opposition between the representatives of ecclesiastical and secular/aristocratic authority on the one hand and the serfdom on the other, and is most thoroughly addressed through the relationship between patriarch and brave (bandit) nobles. With their bold opposition to the patriarch, secret conspiracy and efforts to remedy injustice and restore peace and order in their home country, the nobles also serve as a model for unification of the nation. Exile is also understood in terms of the individual's exile and the search for one's identity. More specifically, it is self-exile, which is at the same time self- awareness, as embodied in the central figure of Jerko, who is torn between the sword, the monk's habit and the poetry/art/spirituality. Jerko could be the alter ego of the writer France Bevk, who wrote the novel under conditions of house imprisonment and concluded it meaningfully with the symbolism of the falcon as the messenger of the spiritual world (and thus art).
Keywords: historical prose fiction; chivalric novel; Middle Ages; occupied Primorsko; novel metaphor; national consciousness